Modernizarea serviciilor judiciare în Republica Moldova prin implementarea tehnologiilor informaționale [Articol] - Țurțurica, Maria-Cristina (Tipografia Artpoligraf, 2021)
The modernization of judicial services is a paramount necessity of our times. The e-justice trend has been strongly catalyzed by the global COVID-19 pandemic. The automation of the judiciary in the Republic of Moldova began in 2007. Specifically, due to the efforts and progress of modernizing the activity of the courts over the years, the Moldovan judiciary was able to continue its activity and did not stop examining the most pressing cases in 2020-2021, despite the ongoing epidemiological crisis. This article describes the peculiarities and benefits of the technological solutions currently used in the Moldovan courts. At the same time, it mentions the prerequisites that must be ensured for the implementation of the modern IT solutions, so that the rights of case participants are observed, and that access to justice for vulnerable and geographically disadvantaged groups is not limited
MODERNIZATION OF JUDICIAL SERVICES IN THE REPUBLIC OF MOLDOVA VIA IMPLEMENTATION OF INFORMATION TECHNOLOGIES
Keywords: information technologies; e-justice; videoconference